Political business cycles, bank pricing behaviour and financial inclusion in Africa - Abdul Ganiyu Iddrisu; Festus Ebo Turkson (Cogent Economics & Finance, 2020)
This paper analyses financial inclusion in Africa focusing on the role of political business cycles and pricing behaviour of banks. We employ a sample of 330 banks operating in 29 African countries to test for two related hypotheses. Panel fixed and random effects were estimated for the period 2002 to 2013. The regression results that ensued suggests first that loan price increases in pre-election and election years. Building on this result and employing various specifications of financial inclusion, the second results suggest that, high bank loan prices in election years tend to increase financial access more, compared to non-election years, and that, high deposit price reduces financial usage but increases financial access in election years, compared to non-election years. By extension, these results have important policy implications for policymakers.
Keywords: P16; D72; E43; G02; 330; political business cycles; election; banks' pricing behaviour; financial inclusion; Africa